A Portable Chip-Based NMR Relaxometry System With Arbitrary Phase Control for Point-of-Care Blood Analysis. - Dreyer, Frederik; Yang, Qing; Alnajjar, Belal; Kruger, Daniel; Blumich, Bernhard; Anders, Jens (Ieee Transactions on Biomedical Circuits and Systems, 2023)
In this article, we present a portable NMR relaxometry system optimized for the point-of-care analysis of body liquids such as blood. The presented system is centered on an NMR-on-a-chip transceiver ASIC, a reference frequency generator with arbitrary phase control, and a custom-designed miniaturized NMR magnet with a field strength of 0.29 T and a total weight of 330 g. The NMR-ASIC co-integrates a low-IF receiver, a power amplifier, and a PLL-based frequency synthesizer on a total chip area of 1100 × 900 μm 2. The arbitrary reference frequency generator enables the use of conventional CPMG and inversion sequences, as well as modified water-suppression sequences. Moreover, it is used to implement an automatic frequency lock to correct temperature-induced magnetic field drifts. Proof-of-concept measurements on NMR phantoms and human blood samples show an excellent concentration sensitivity of v[Formula: see text] = 2.2 mM/[Formula: see text]. This very good performance renders the presented system an ideal candidate for the future NMR-based point-of-care detection of biomarkers such as the blood glucose concentration.
EVALuna2:595043